Interaction insect-microorganisms producers of ochratoxin A infesting cocoa (Theobroma cacao) bean stocks from Tonkpi region, Western in Co´te d Ivoire - Tatiana-Therese, Tah Gueu; Nondenot, Aboua Louis Roi; Christian, Tano DjeKevin; Ardjoumani, Dembele (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
The storage of cocoa beans in humid tropical area lead to their infection by insects and mold. The objectives of the current study were to make an inventory of insects and molds producing ochratoxin A and to highlight the type of relationship between the incriminate insects and the molds. During the two cocoa campaigns respectively between april and august 2014 and between october 2014 and february 2015, 6 lots of dried beans respectively at each campaign, have been constituted and put in 5 Kg bags. The lots have been analyzed each month during a period of 5 months. The micro-flora has been isolated by the dilution method on Sabouraud agar of chloramphenicol. The developed strains have been identified according to Samson and al. classification. The colonies have been enumerated according to the recommended formula by the French Association for Standardization (AFNOR). We found 6 and 3 Aspergillus species respectively during the small and great campaign and only a Penicillium species during both campaigns. The enumeration after shifting revealed 5 and a single species respectively of Beetles and Lepidoptera at the small campaign and 3 species of Beetles and a single species of Lepidoptera during the great campaign. Two types of relationship were established between insects and molds in cocao bean stocks, the commensalism and the symbiosis. This study revealed more contamination by the insects and molds during the small campaign.